Handbook of research on transmedia storytelling and narrative strategies - Yilmaz, Recep; Erdem, M. Nur, 1976-; Resuloglu, Filiz, 1981- (Hershey, PA : Information Science Reference, 2018)
'This book explores the concept of transmedia storytelling, which is closely related to concepts of convergency, multimedia and intertextuality. It is defined as a process where integral elements of a fiction get dispersed systematically across multiple delivery channels to create a unified and coordinated entertainment experience'--
Keywords: Narration (Rhetoric).; Storytelling in mass media; Digital storytelling